BUDAYA ARAB PRA DAN PASCA ISLAM - Syafichrul Umam. Fat Han F; Nadamaula Nafa; Lilik Dzuriyyah; Istantina Nia AR (SABANA: Jurnal Sosiologi, Antropologi, dan Budaya Nusantara, 2023)
The social condition of the Arab nation before Islam was known as the ‘age of ignorance’ or the era of ignorance, which was caused by social, political, moral and social relations in a state of real error. In order to understand the customs of the ignorance of the Arabs, God sent a Messenger, Muhammad. In this study, researchers discussed the integration of Islam and Arabic culture in both pre- and post-Islamic times. The research method used is the Sociology of Religion approach, and in its refinement it will be supported by other approaches such as the Phenomenological, Historical and Anthropological approaches. The results of the research show that many of the pre-Islamic Arab nations worshiped idols, the political conditions at that time were divided, not recognizing central leadership or unity. While the condition of the post-Islamic Arab nation, the population has lived in prosperity. Changes both in terms of character, culture and beliefs. So that the Arabs at that time respected each other and because of that it was also detrimental to the disputes between tribes that often occurred during the Jahiliyya period.